Drum Cutting Specific Energy Consumption Model Built by Cutting Curves Analysis - Gao Kui-Dong; Du Chang-Long; Jiang Hong-Xiang (Institute of Advanced Engineering and Science, 2013)
For so much error caused in drum’s cutting specific energy consumption calculation when using sharp cutter’s cutting specific energy formula, the drum’s torque mathematical model and cutting specific energy consumption mathematical model which took Goktan’s conical pick cutting mathematical model as basic was established refer to the drum cutting curves of the sequence drum, the punnett square drum, the aberrance 1 drum and the aberrance 2 drum. The tests of four type drums and four sequence drums which installed different cone angles were carried out in cutting test bed. The results indicate that: the similarity of calculate result and test result can support the theoretical research;cutting torque and cutting specific energy consumption rise with the cone angle increasing; the minimum torque and cutting specific energy consumption was produced by 2-starts vane punnett square drum, 3-tarts vane aberrance drums produced more larger torque and cutting specific energy consumption；Using punnett square drum in coal cutting can reduce cutting specific energy consumption, but 3-tarts vane aberrance drums have no advantage compared with 2-tarts vane sequence drum in reducing cutting specific energy consumption. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2869